2006
DOI: 10.1176/appi.ajp.163.3.387
|View full text |Cite
|
Sign up to set email alerts
|

PET Study Examining Pharmacokinetics, Detection and Likeability, and Dopamine Transporter Receptor Occupancy of Short- and Long-Acting Oral Methylphenidate

Abstract: The findings suggest that the abuse potential of oral methylphenidate is strongly influenced by the rate of delivery and not solely by the magnitude of plasma concentration or brain transporter occupancy. These results advance understanding of the underlying central effects of methylphenidate in humans and identify a potentially less abusable methylphenidate formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
120
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(132 citation statements)
references
References 27 publications
(33 reference statements)
8
120
0
4
Order By: Relevance
“…Spencer et al (2006) have subsequently provided confirmatory PET data illustrating how striatal effects of MPH match behavioral effects using immediate and extended release formulations of MPH. Recent study in ADHD adults has also shown depressed dopamine activity in the caudate, and possibly some default network regions (amygdala/hippocampus) were associated with inattention .…”
Section: Functional Studies: Pet and Fmrimentioning
confidence: 92%
See 1 more Smart Citation
“…Spencer et al (2006) have subsequently provided confirmatory PET data illustrating how striatal effects of MPH match behavioral effects using immediate and extended release formulations of MPH. Recent study in ADHD adults has also shown depressed dopamine activity in the caudate, and possibly some default network regions (amygdala/hippocampus) were associated with inattention .…”
Section: Functional Studies: Pet and Fmrimentioning
confidence: 92%
“…Both SPECT and PET have generally been supplanted by fMRI for functional studies, as fMRI offers superior spatial and temporal resolution, and SPECT and PET's use of radiopharmaceuticals makes it ethically difficult to justify their use in healthy volunteers, especially children (Castellanos, 2002). However, both SPECT and PET still have important uses that other non-invasive techniques do not offer, such as neurotransmitter receptor characterization, measurement of dopamine transporter (DAT) levels, and quantification of extracellular dopamine Spencer et al, 2006Spencer et al, , 2005Volkow et al, 2005Volkow et al, , 2007. Early SPECT studies suggested striatal/basal ganglia abnormalities (Lou et al, 1984(Lou et al, , 1990(Lou et al, , 1989, despite some methodological issues (Castellanos, 2002).…”
Section: Functional Studies: Pet and Fmrimentioning
confidence: 99%
“…PET and SPECT studies have detected NT release in response to pharmacological challenges, including amphetamine (e.g., Dewey et al, 1993;Innis et al, 1992;Laruelle et al, 1995;Mach et al, 1997), cocaine (Mach et al, 1997;Volkow et al, 1999), methylphenidate (Mach et al, 1997;Spencer et al, 2006;Volkow et al, 1999;Volkow et al, 1994) and other drugs, as well as behavioral challenges such as videogaming (Koepp et al, 1998), gambling and monetary reward (Pappata et al, 2002;Zald et al, 2004), and other tasks. In conventional PET analyses, NT release is detected by change in binding potential (BP: e.g., Logan et al, 1996;Logan et al, 1990), an index of the time-averaged decrease in receptor availability from baseline to activation condition.…”
Section: Introductionmentioning
confidence: 99%
“…However, the time course of neurotransmitter release in response to specific stimuli has not been measured in humans and may encode pertinent information about brain function. It has been hypothesized that the speed of dopamine release elicited by a drug may be a strong indicator of the drug's addictive liability and potential for abuse (Spencer et al, 2006;Volkow et al, 1995;Volkow et al, 1999;Volkow and Swanson, 2003). Boileau et al (2007) speculated that amphetamine-and placebo-induced dopamine responses may follow distinct time courses, but noted that PET was not capable of distinguishing such differences.…”
Section: Introductionmentioning
confidence: 99%
“…One study 7 showed that OROS methylphenidate had no detection or likeability in subjects tested every hour for 10 hours after ingestion.…”
Section: Stimulant Treatmentmentioning
confidence: 99%